Agent based approaches for smart charging strategy for electric vehicles - Ferreira, João C. (2011)
This paper presents an agent process simulation to control and monitor the Electric Vehicle charging process, using existing power distribution limitations and microgeneration capacity. The goal is to simulate the consumers’ energy consumption and their unexpected behavior, using past experience and taking into account distribution network and home power limitation to find an intelligent charging pattern. This paper proposes a novel approach for this problem based on an agent-based simulation platform where stochastic process is adopted to perform unexpected user behavior. This simulation tool can be used to determine the capability of the actual electrical distribution network for supply energy to the final consumers and for charge the bank of batteries of electrical vehicles, which can occur simultaneously.